2022
DOI: 10.3389/fneur.2022.900438
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Association Between Asthma and the Risk of Stroke

Abstract: IntroductionAsthma and stroke share many risk factors. Previous meta-analysis has indicated that asthma is associated with an increased risk of stroke. However, this study were limited by the small number of articles included and the lack of subgroup analyses of different stroke types and different populations. This meta-analysis aimed to synthesize evidence systematically to investigate the impact of asthma on stroke.MethodsWe searched Medline (via PubMed), Web of Science and EMBASE databases and manually ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
3
0
3
Order By: Relevance
“…согласно результатам многочисленных исследований, анализ параметров жёсткости сосудистой стенки -важный аспект для стратификации сердечно-сосудистого риска и оценки эффективности лечения [6]. предпосылкой для изучения параметров суточной артериальной ригидности стали данные о том, что у пациентов с бронхиальной астмой риск сердечнососудистой заболеваемости выше в сравнении с общей популяцией [5], а ранее проведенные однократные исследования жёсткости сосудистой стенки выявили изменения у больных астмой.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…согласно результатам многочисленных исследований, анализ параметров жёсткости сосудистой стенки -важный аспект для стратификации сердечно-сосудистого риска и оценки эффективности лечения [6]. предпосылкой для изучения параметров суточной артериальной ригидности стали данные о том, что у пациентов с бронхиальной астмой риск сердечнососудистой заболеваемости выше в сравнении с общей популяцией [5], а ранее проведенные однократные исследования жёсткости сосудистой стенки выявили изменения у больных астмой.…”
Section: Discussionunclassified
“…изучение маркеров субклинического поражения сосудистой стенки, а именно артериальной жесткости, имеет большое значение как способ улучшения стратификации сердечно-сосудистого риска, выявления лиц с доклиническим атеросклерозом и принятия соответствующих мер для замедления этого процесса [4]. в настоящее время широко используются методы однократного измерения артериальной ригидности, однако возможность анализа осциллометрической кривой в аппаратах суточного мониторирования артериального давления (смАд) позволяет получить информацию в отношении суточного профиля жесткости артерий, что представляет значительный интерес [5].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Therefore, PD may be one of several clinical presentations associated with asthma that share the same underlying mechanism. In addition, it is commonly seen that asthma and PD have similar comorbidities, such as dyslipidemia [ 49 , 50 , 51 ], coronary heart disease [ 15 , 52 , 53 ], and depression [ 15 , 22 , 54 ], which may imply that the two conditions have a shared pathogenesis and similar preventive treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis of cohort studies, asthma increased the risk of CVD death (Risk ratio (RR): 1.25, 95% confidence interval (CI): 1.14-1.38) [4]. Regarding subtypes of CVD, patients with active asthma had a higher risk of stroke, especially ischemic stroke, but inactive asthma was not associated with an increased risk of stroke in a recent meta-analysis of observational studies [5]. Another meta-analysis of cohort studies reported that asthma increased risk of subsequent coronary heart disease in women over 18 years of age, but statistical heterogeneity was high across studies [6].…”
mentioning
confidence: 99%